2014
DOI: 10.1186/1756-0500-7-838
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis B and C viruses and risk factors in HIV infected children at the felgehiwot referral hospital, Ethiopia

Abstract: BackgroundLiver hepatitis due to Hepatitis B (HBV) and hepatitis C virus (HCV) co-infection is the leading cause of morbidity and mortality in HIV infected children and it is more severe in resource poor settings. Data on seroprevalence of HBV and HCV among HIV infected children are scarce in Ethiopia. This study was conducted to determine seroprevalence and risk factors of HBV and HCV and its effect on liver enzyme among HIV-positive children aged 18 months to 15 years attending the paediatric HIV care and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
38
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 26 publications
16
38
5
Order By: Relevance
“…This result is close to the 0.46% rate reported by Kerubo et al in Kenya, and to the 0.7% rate reported by Chiekulie et al in Nigeria among adults [16,17]. Abera et al had reported a higher rate of 5.5% [5]. Only one patient involved in the study presented with a triple co-infection.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…This result is close to the 0.46% rate reported by Kerubo et al in Kenya, and to the 0.7% rate reported by Chiekulie et al in Nigeria among adults [16,17]. Abera et al had reported a higher rate of 5.5% [5]. Only one patient involved in the study presented with a triple co-infection.…”
Section: Discussionsupporting
confidence: 87%
“…It is close to the one found out by several authors; this suggests a perinatal infection or an infection in early childhood of hepatitis among those children [5,6]. As the risk for transition from chronicity to HBV infection is higher in case of infection in early childhood, it is necessary to ensure prevention through immunization at birth in countries with high prevalence [19].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations